Security risk evaluation for logic locking - Diao, Shengjia (Nanyang Technological University, 2024)
The Integrated Circuit (IC) supply chain is facing multiple challenges as the globalization develops. Untrustworthy entities like chip manufacturers violated the intellectual properties and cause enormous economic loss. This circumstance highlights a necessity of robust logic obfuscation solutions to eliminate the dangers to the greatest extent and a comprehensive security evaluation system on those solutions keep abreast of the times. Boolean Satisfiability (SAT) attacks can almost break all existent logic obfuscation techniques. It is accepted as a powerful tool to assess the security of the logic obfuscation methods by the academia as well. However, the SAT attack faces significant challenges of logic locking on complex circuits, especially multipliers.